Hypervalent iodine-catalyzed amide and alkene coupling enabled by lithium salt activation - Chhikara, Akanksha; Wu, Fan; Kaur, Navdeep; Baskaran, Prabagar; Nguyen, Alex M.; Yin, Zhichang; Pham, Anthony H.; Li, Wei (Beilstein Journal of Organic Chemistry, 2024)
Hypervalent iodine catalysis has been widely utilized in olefin functionalization reactions. Intermolecularly, the regioselective addition of two distinct nucleophiles across the olefin is a challenging process in hypervalent iodine catalysis. We introduce here a unique strategy using simple lithium salts for hypervalent iodine catalyst activation. The activated hypervalent iodine catalyst allows the intermolecular coupling of soft nucleophiles such as amides onto electronically activated olefins with high regioselectivity.
Keywords: amide coupling; hypervalent iodine catalysis; lithium salt activation; olefin oxyamination; oxazoline